2009
DOI: 10.1183/09031936.00164408
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of asthma phenotypes in supermarket bakery workers

Abstract: While baker's asthma has been well described, various asthma phenotypes in bakery workers have yet to be characterised. Our study aims to describe the asthma phenotypes in supermarket bakery workers in relation to host risk factors and self-reported exposure to flour dust.A cross-sectional study of 517 supermarket bakery workers in 31 bakeries used a questionnaire, skin prick tests, and specific immunoglobulin E to wheat, rye and fungal aamylase and methacholine challenge testing.The prevalence of probable occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 35 publications
2
37
0
3
Order By: Relevance
“…A cross-sectional study of 517 supermarket bakery workers employed in 31 bakeries used a European Community Respiratory Health Survey questionnaire, skin prick tests for atopy, and specific IgE to flour dust allergens and methacholine challenge testing 16. While all permanent (n=318) and casual workers (n=168) in the bakery and ex-bakers with asthma redeployed from the bakery section 2 years prior to the study (n=31) were investigated in the initial study, only permanent and casual workers were included in this current analysis since no data on current exposures were available for the ex-baker group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study of 517 supermarket bakery workers employed in 31 bakeries used a European Community Respiratory Health Survey questionnaire, skin prick tests for atopy, and specific IgE to flour dust allergens and methacholine challenge testing 16. While all permanent (n=318) and casual workers (n=168) in the bakery and ex-bakers with asthma redeployed from the bakery section 2 years prior to the study (n=31) were investigated in the initial study, only permanent and casual workers were included in this current analysis since no data on current exposures were available for the ex-baker group.…”
Section: Methodsmentioning
confidence: 99%
“…This study is based on the results of a detailed health survey of South African bakery workers 16. The exposure estimates for wheat allergen used in the current study were based on baseline measurements of a subgroup of supermarket bakery workers previously reported 17.…”
Section: Introductionmentioning
confidence: 99%
“…For bakers, the greatest reduction in flour dust was achieved with control measures such as the use of a mixer lid (67 %), divider oil (63 %), or focused training (54 %). However, the greatest reduction (80 %) was observed when using a combination of all control measures (Baatjies et al 2009). …”
Section: Introductionmentioning
confidence: 94%
“…There has recently been a dramatic increase in the number of in-store franchise bakeries in Northern Europe and South Africa. 2,3 Studies conducted among bakery workers have reported the prevalence of baker asthma to be 5 to 17%. 4 Respiratory symptoms in bakery workers have commonly been attributed to the exposure to wheat flour proteins and the enzymes used to improve dough flavor.…”
mentioning
confidence: 99%
“…6 Atopy has also been found to be an important independent risk factor for the development of baker asthma, 7 and at least one previous study has examined the prevalence of different asthma phenotypes in bakery workers. 3 Baker asthma is associated with prolonged exposure to flour dust that includes a complex mixture of proteins and other organic materials, including the bacterial endotoxin, lipopolysaccharide (LPS). 8 LPS stimulates an inflammatory response by ligating the Toll-like Receptor 4 (TLR4) receptor and its coreceptor CD14.…”
mentioning
confidence: 99%